Kemampuan Menentukan Bentuk dan Makna Majas pada Siswa Kelas IX MTSN 3 Banjarmasin - Ngatiyem Ngatiyem (Jurnal Hadratul Madaniyah, 2017)
This study deals with the ability to determine the shape and meaning of majas in grade IX students of MTsN 3 Banjarmasin. The purpose of the study is 1) Describing the ability to learn the significance and meaning of the comparison subject in class IX MTsN 3 Banjarmasin. 2) Describes the ability to determine the sense and meaning of majing for class IX students of MTsN 3 Banjarmasin. 3) Represents the ability to learn the purpose and meaning of majing in class IX students of MTsN 3 Banjarmasin. 4) Describes the ability to determine the shape and meaning of majing for grade IX students of MTsN 3 Banjarmasin. This research uses a quantitative descriptive method. The place of research carried out was at IX MTsN 3 Banjarmasin, and 90 class IX people were made into the study population, while for the sample totalling 50 students. To get technical data in the form of tests to measure students' ability in determining the form and meaning of majas. Data processing from the test results, the scores obtained are converted to eleven (stanel) scale standard values, the students' scores are as follows: (1) excellent title contains 2 students or 4%, (2) good grades turn out to be 28 students or 56 %, (3) there are less than 7 students or 14%, (3) failing predicate contains 13 students or 26%. Based on the results of data processing that has been converted, it can be concluded that students who earn as many as 30 students or 60%, and students who have not been able to produce as many as 20 students or 40% of all samples.